Penetapan Jumlah Mahar yang Disesuaikan Waktu Pernikahan Menurut Hukum Islam - Azizah, Nurul; Fahrun Dama; Sutopo, Sutopo (HOKI : Journal of Islamic Family Law, 2023)
Dowry is something that must be given by a man to a woman in order to gain control over all of her limbs. This research wants to find out how the law determines the amount of dowry in marriage customs according to Islamic law in the village of Gunung Teguh Sangkapura. This study uses a descriptive analysis methodology with a qualitative approach and field research, which is in the form of a field, namely by going directly to the field to explore the practice of giving dowry which is adjusted to the time of the wedding and interviewing the bride and groom. The results of this study indicate that the determination of dowry according to the Imams of 4 schools of thought is not interpreted as payment, but is intended to elevate the dignity of women who since the time of ignorance had their dignity trampled upon.